2017
DOI: 10.30539/iraqijvm.v41i1.71
|View full text |Cite
|
Sign up to set email alerts
|

Determination the causative strain for hydatid cyst in Iraqi cattle by using ND1 gene

Abstract:      Hydatid Cysts were obtained from 15 cows from liver, lung, spleen, heart, and peritoneal cavity, between December 2014 and October 2015. Hydatid cysts (protoscoleces) were used for deoxyribonucleic acid extraction by using mechanical grinder. The purification of mtDNA was done by (promega kit, USA). The mitochondrial NADH dehydrogenase subunit 1 (ND1) genes was used as targets for polymerase chain reaction amplification, all hydatid cysts yielded amplification products. Polymerase chain reaction p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…On the other hand, Baraak et al (21), and Muhaidi et al (22) demonstrated that G1 (sheep strain) genotype was the predominant isolate of various organs of human and cow, respectively. However, authors believed that G1 could produce unusual lesions like that of E. multilocularis (23). The predominance of G1 genotype (sheep strain), in this article results agree with most previous studies (24), and this may indicate that G1 strain is prevalent in endemic areas like Iraq in both man and animals.…”
Section: Discussionsupporting
confidence: 90%
“…On the other hand, Baraak et al (21), and Muhaidi et al (22) demonstrated that G1 (sheep strain) genotype was the predominant isolate of various organs of human and cow, respectively. However, authors believed that G1 could produce unusual lesions like that of E. multilocularis (23). The predominance of G1 genotype (sheep strain), in this article results agree with most previous studies (24), and this may indicate that G1 strain is prevalent in endemic areas like Iraq in both man and animals.…”
Section: Discussionsupporting
confidence: 90%
“…Whereas, sheep were G1 (80%) and G3 (20%). Mustafa et al, (2019), AL-Asadi et al, (2021), Muhaidi et al, (2017, Muhaidi et al, (2018) identified E.granulosus in terms of ND1 gene as G1 genotype sheep strain (100%). The Iraqi isolates are consistent with the isolates of other countries, such as, Turkey (Barazesh et al, 2019), Iran (Barazesh et al 2019;Hajialilo et al, 2012;Pezeshki et al, 2013;Sharbatkhori et al, 2016), Sudan (Ahmed et al, 2018), Egypt (Amer et al, 2015), Uzbekistan (Kim et al, 2020), Peru (Sánchez et al 2012;Sánchez et al, 2010) and China (Ohiolei et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the cysts had three walls and hydatid sand within. The fertility of these cysts was then assessed by counting the protoscolex using the procedure reported by Muhaidi et al [ 18 ], and the protoscolex was separated.…”
Section: Methodsmentioning
confidence: 99%